Lactic Acid Production from High Concentration of Invert Sugar in Semi-Batch Reactor - R Sirisangsawang; P Kitchaiya (My University, 2020)
Abstract The objective in this study is the production of high yield of lactic acid production from invert sugar in alkaline degradation at mild reaction condition. The invert sugar was immediately and continuously added into an alkaline solution in a batch and semi-batch reactor, respectively. The effect of batch and semi-batch, initial concentration of sodium hydroxide and initial of concentrated raw materials were studied. Semi-batch provided better yield than batch reactor. High sodium hydroxide concentration with low invert sugar in semi-batch operation was found to have high lactic acid. The feed concentration of invert sugar at 30, 45 and 70% provided lactic acid yield around 65-68% for excess sodium hydroxide base at 50°C and 10 hr.
Keywords: Sodium hydroxide; Batch reactor; Biofuel production and bioconversion